Clustering and Standard Error Bias in Fixed Effects Panel Data Regressions - Moody, Carlisle Eaton (Journal of quantitative criminology, 2020)
We address several issues concerning standard error bias in pooled time-series cross-section regressions. These include autocorrelation, problems with unit root tests, nonstationarity in levels regressions, and problems with clustered standard errors.